Pengembangan Sistem Informasi Pendataan Alumni berbasis Web pada SMA Negeri 3 Pontianak - Egy Ihza Madhani; Satrio Agung Wicaksono; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Management of alumni data at SMA Negeri 3 Pontianak is still done manually, namely by printing in the form of alumni books or class books. By using a printed book, the stored data cannot be changed. Alumni need the latest information from the school, for example cases when alumni who have just graduated want to take care of administration to schools such as legalizing diplomas and SKHU. Based on these problems, an alumni data collection information system was built using an iterative model. Data was collected by interviewing and observing PKU teachers as well as technicians at SMA Negeri 3 Pontianak. The needs analysis was compiled based on the results of follow-up interviews with the same teacher and a number of 2017 and 2019 alumni. In each iteration, the system design uses Unified Modeling Language (UML) diagrams. The implementation uses the MVC (Model, View, Controller) concept with the third version of the CodeIgniter framework. Furthermore, using black-box testing with 17 functional requirements tested and the results are smooth and 100% valid. In the first iteration User Acceptance Testing (UAT), testing was carried out on alumni who showed a Likert scale value of 347. In the second iteration User Acceptance Testing (UAT) was carried out for admins and students. The Likert scale value for admin is 50 and for students is 320. The level of user approval for the system is 92.5% for alumni, 100% for teachers, and 85.3% for students, which means this system can be accepted by the school, alumni, and student.